Influence of Twitter social network graph topologies on traditional and meme stocks during the 2021 GameStop short squeeze - Daniel Verdear; Neil F. Johnson; Stefan Wuchty (npj Complexity)
Abstract In early 2021, groups of Reddit and Twitter users collaborated to raise the price of GameStop stock from $20 to $400 in a matter of days. The heavy influence of social media activity on the rise of GameStop prices can be contrasted with the muted social media influence on other, more traditional stocks. While traditional stocks are modeled quite successfully by current methods, such methods break down when used to model these so-called meme stocks. Our project analyzes the graph topology of retweet graphs built from GameStop-related tweets and other meme stocks to find that the clustering coefficient and network diameter of a retweet graph can be used to decrease the mean absolute error of meme stock trading volume predictions by as much as 46% over the control group during the first 70 trading days of 2021.